Factors and types of error that contributes to the difficulties in solving Mathematical problems among Year 5 pupils in SK Goebilt, Kuching / Hardi Rasidi - Rasidi, Hardi (2016)
The objectives of this research are to identify the factors and types of algorithm error that contributes to difficulties in solving mathematical word problems. Research respondents are 18 pupils from 2 different class of year 5 at SK Goebilt, Petra Jaya, Kuching, Sarawak. Samples are chosen using stratified sampling. This research used test that contains 10 questions. The test results and findings are analyzed using descriptive statistics. In this research, pupils were tested using a set of 10 question of mathematical word problem. After the test, pupils will be interviewed based on Newman Error Analysis Procedure that had been modified to analyze the problems and mistakes. The results show that factors that contribute to difficulties in solving mathematical word problems are reading, understanding, transforming word problem, applying process skill and encoding. Meanwhile, for the types of algorithm errors are careless, computation error, wrong writing, wrong place value and others. This factors and types of errors occur during the test especially in applying process skill in the questions and making more computation error when answering the questions. Teachers must play their role at school with creative and innovative lessons so that pupils will be able to develop their thinking skills while solving mathematical word problem questions.